The autophagy protein ATG-9 promotes aversive learning in Caenorhabditis elegans through trafficking neuropeptide receptors - Wai Hou Tam; Yu-Cheng Tang; Hao-Han Shiu; Shang-Heng Tsai; Pei-Shu Jao; Chun-Liang Pan (Proceedings of the National Academy of Sciences, 2026)
Autophagy is a degradative process that maintains cellular homeostasis. Autophagy biogenesis occurs at synapses, but its impact on synaptic functions is incompletely understood. Here we show that, in Caenorhabditis elegans , synaptic ATG-9, the only transmembrane autophagy protein, contributes to aversive learning under mitochondrial stress. Analysis of the neuronal translatome reveals that autophagy is upregulated by stress in the octopaminergic RIC neuron and it promotes aversive learning. Inactivating autophagy genes, including atg-9 , reduces aversive learning. Mitochondrial stress increases synaptic ATG-9 through AP-1- and AP-2-dependent exocytosis and endocytosis, respectively, and reducing synaptic ATG-9 impairs aversive learning. We further identify the FRPR-6 neuropeptide receptor as a substrate of ATG-9 modulation. Both atg-9 and frpr-6 promote aversive learning and RIC activities, and the abundance of FRPR-6 in the RIC neurite depends on atg-9 . We postulate that ATG-9-containing synaptic compartments promote neuronal plasticity through modulating receptor trafficking to enable aversive learning under systemic mitochondrial stress.